2023
DOI: 10.3389/fnhum.2023.1151531
|View full text |Cite
|
Sign up to set email alerts
|

A review on multiple sclerosis prognostic findings from imaging, inflammation, and mental health studies

Abstract: Magnetic resonance imaging (MRI) of the brain is commonly used to detect where chronic and active lesions are in multiple sclerosis (MS). MRI is also extensively used as a tool to calculate and extrapolate brain health by way of volumetric analysis or advanced imaging techniques. In MS patients, psychiatric symptoms are common comorbidities, with depression being the main one. Even though these symptoms are a major determinant of quality of life in MS, they are often overlooked and undertreated. There has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 131 publications
0
8
0
Order By: Relevance
“…In this aspect, a recent, comprehensive review highlighted the potential significant role of nutritional lifestyle and physical activity in MS pathogenesis and management [ 65 ]. This narrative review underlined that low-carbohydrate, Mediterranean, and fast-mimicking diets have shown both in animal models and in humans a positive effect on MS course and in patient-reported outcomes [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this aspect, a recent, comprehensive review highlighted the potential significant role of nutritional lifestyle and physical activity in MS pathogenesis and management [ 65 ]. This narrative review underlined that low-carbohydrate, Mediterranean, and fast-mimicking diets have shown both in animal models and in humans a positive effect on MS course and in patient-reported outcomes [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this aspect, a recent, comprehensive review highlighted the potential significant role of nutritional lifestyle and physical activity in MS pathogenesis and management [ 65 ]. This narrative review underlined that low-carbohydrate, Mediterranean, and fast-mimicking diets have shown both in animal models and in humans a positive effect on MS course and in patient-reported outcomes [ 65 ]. The authors supported that MD may be easier to be maintained compared to fast-mimicking and low-carbohydrate diets, which could lead to detrimental side effects, requiring careful-clinical monitoring [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 Despite its importance, mental health remains overlooked in this patient group. 28 Treating psychiatric symptoms is crucial to enhance mental health, which may further improve the quality of life and sleep quality of peoples with MS. 29,30 In this aspect, nutrition may act as a possible co-factor influencing the inflammatory cascade by acting on both on the molecular pathways and gut microbiota involved in MS. 31 Alarmingly enough, the question whether dietary habits and lifestyle may positively influence on the course of MS remains an extremely matter of debate, while the potential benefits from any health dietary pattern diet in MS have not yet been proven by strong evidence. [32][33][34] In this aspect, there are several evidence that nutritional assessment and support may exert crucial impacts by slowing down the development and progression as well as by monitoring peoples with neurodegenerative diseases, including MS. 35 In support of this view, there is recent preliminary evidence that a high intake of saturated fat increased the incidence of MS, while unsaturated fatty acids may exert a positive effect on the course of MS. 36,37 Notably, there are some pilot studies that some healthy dietary patterns such as low-fat vegan, modified Paleolithic, and gluten free diets as well as Mediterranean diet (MD), and intermittent fasting have been associated with an improvement of disease disability and symptom severity.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Despite its importance, mental health remains overlooked in this patient group. 28 Treating psychiatric symptoms is crucial to enhance mental health, which may further improve the quality of life and sleep quality of peoples with MS. 29,30…”
Section: Introductionmentioning
confidence: 99%